Secondary aerosol formation promotes water uptake by organic-rich wildfire haze particles in equatorial Asia - Chen, Jing (2018)
The diameter growth factor (GF) of 100nm haze particles at 85% relative humidity (RH) and their chemical characteristics were simultaneously monitored at Singapore in October 2015 during a pervasive wildfire haze episode that was caused by peatland burning in Indonesia. Non-refractory submicron particles (NR-PM1) were dominated by organics (OA; approximating 77.1% in total mass), whereas sulfate was the most abundant inorganic constituent (11.7% on average). A statistical analysis of the organic mass spectra showed that most organics (36.0% of NR-PM1 mass) were highly oxygenated. Diurnal variations of GF, number fractions of more hygroscopic mode particles, mass fractions of sulfate, and mass fractions of oxygenated organics (OOA) synchronized well, peaking during the day. The mean hygroscopicity parameter (κ) of the haze particles was 0.189±0.087, and the mean κ values of organics were 0.157±0.108 (κorg, bulk organics) and 0.266±0.184 (κOOA, OOA), demonstrating the important roles of both sulfate and highly oxygenated organics in the hygroscopic growth of organics-dominated wildfire haze particles. κorg correlated with the water-soluble organic fraction insignificantly, but it positively correlated with f44 (fraction of the ion fragment at m∕z44 in total organics) (R=0.070), implying the oxygenation degree of organics could be more critical for the water uptake of organic compounds. These results further suggest the importance of sulfate and secondary organic aerosol formation in promoting the hygroscopic growth of wildfire haze particles. Further detailed size-resolved as well as molecular-level chemical information about organics is necessary for the profound exploration of water uptake by wildfire haze particles in equatorial Asia.